Phytochemical Screening and Cytotoxicity Evaluation of Ethanolic Extract of Hypericum cordifolium (choisy) Leaves - Basyal, Deepak; Bhandari, Netra Lal (Journal of Nepal Chemical Society, 2019)
Hypericum cordifolium is a medicinal plant traditionally used for the treatment of the menstrual disorder, backache, dislocation of bone, fever, diarrhea and dysentery due to the presence of potential bioactive secondary metabolites. Ethanolic extract of dried leaf powder was prepared using the Soxhlet apparatus, followed by qualitative phytochemical screening with different reagents. In-vitro cytotoxicity assay was screened by using brine shrimp bioassay and LC50 was calculated by probit analysis. Alkaloids, glycosides, amino acids, and fixed oils were present at very minute level whereas saponin, phenol and flavonoids were present at significant level. Cytotoxicity assay of the leaf extract showed significant results (p<0.05).LC50 of 273 ppm, which was less than 1000 ppm, showing that the plant is toxic. The study revealed that the plant possessed medicinal values, which could justify the ethno-medicinal importance scientifically. This research has pointed out further possibilities of works to be done on this virgin plant creating the opportunity for scientific researches to give birth of potent lead molecules.